Pharmacological management of obstetric hemorrhage - Yarotsky, Rostyslav; Klymenko, Olena (The Ukrainian Scientific Medical Youth Journal, 2025)
postpartum hemorrhage is an emergency in obstetrics, which is one of the five most common causes of maternal mortality. Knowledge of all algorithms and protocols for childbirth, providing assistance in the event of an emergency is the key to reducing maternal mortality and delayed negative health consequences for both the mother and the newborn. The aim of the work was to study the protocols and management of postpartum obstetric hemorrhage. Upon hospitalization, the pregnant woman undergoes laboratory and instrumental examination, the doctor assesses the risk group for postpartum obstetric hemorrhage. First pregnancy, 36 weeks. Twin, bichorionic, biamniotic. History of primary infertility. Pregnancy occurred with the use of additional reproductive technologies. According to the results of the examination, moderate preeclampsia, secondary thrombocytopenia were noted. A cesarean section was performed and one of the main points of highly professional care for postpartum hemorrhage is the administration of drugs: a hormonal preparation of the posterior pituitary gland - oxytocin, an agonist of oxytocin receptors - carbetocin, a fibrinolysis inhibitor - tranexamic acid and prostaglandins - misoprostol; to prevent and eliminate hypochromic anemia - iron preparations in accordance with the approved protocol.